A multi-criteria system for performance assessment and support decision-making based on the example of Premier League top football strikers - Kolbowicz, M.; Nowak, M.; Wieckowski, J. (Physical Activity Review, 2024)
The effective management of sports teams plays a pivotal role in achieving substantial success. In this pursuit, an increasing number of teams are resorting to information systems to enhance decision-making processes. These systems ensure the implementation of well-informed decisions, thereby contributing additional insights into training management. Through their assistance, it becomes feasible to optimize both player potential and overall team performance. In this paper, we propose a decision system rooted in the Multi-Criteria Decision Analysis (MCDA) approach, complemented by sensitivity analysis, to assess the performance of soccer players. The evaluation focused on football players in the forward position in the Premier League during the seasons 2015-2021. Subsequently, a sensitivity analysis of the results was conducted to delineate key elements in the game that significantly influence performance quality. Based on these findings, adjustments to a player's training plan can be made, targeting specific aspects of the game to enhance the player's potential. The study's results underscore that, with appropriate enhancements to players' performance, they can achieve markedly superior ratings compared to their counterparts.